DISSEMINATION OF FAKE NEWS, THE COVID-19 PANDEMIC AND CRIMINAL LAW - Miladinović Stefanović, Dušica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The health crisis caused by the global spread of the infectious disease COVID-19 has generated significant changes in many segments of human life, leading to a new narrative on the so-called “new normality”. Without elaborating on the meaning of this phrase and the implications of declaring everything we have been through in the past period as normal, the paper analyzes only one aspect of these changes. It refers to a surge of different (dis)information we have been flooded with from various sources. In theoretical discourse, this phenomenon has already been designated as infodemia, a coined and rather illustrative concept. In the conventional media, and particularly the Internet and social networks, there is a proliferation of ample content on the COVID disease, ways of treatment, the functioning of the economy and crime rates in the new circumstances, etc. The contradictory nature of these contents often causes confusion and panic in the general public, turmoil and disturbance of public order and peace, but it also aggravates the implementation of decisions and measures of state bodies or the functioning of organizations in charge of performing public authorities. The paper is an attempt to critically consider the criminal law reaction to the dissemination of false news in the circumstances of the COVID-19 pandemic. The author first presents the Serbian normative framework on this matter in emergency situations and refers to selected foreign legislations, and then analyzes the available data on the practical application of legal provisions in extraordinary circumstances.
Keywords: fake news; infodemia; COVID-19 pandemic; criminal law; causing panic and disorder